Development of Small Farms in the Agro-Industrial Complex - Петруненко, Ярослав Вікторович; Петруненко, Я. В.; Петруненко, Ярослав Викторович; Petrunenko, Yaroslav V.; Petrunenko, Iaroslav V.; Погріщук, Олег Борисович; Погріщук, О. Б.; Погрищук, Олег Борисович; Pohrishchuk, Oleh B.; Pohrishchuk, Oleg; Плотнікова, Марія Федорівна; Плотнікова, М. Ф.; et al. (John M Jun, 2021)
Modern small farms are important link components in the structure of the world agro-industrial complex. It ensures the food and nutritional sustainability of the country exclusively at the local regional level. The purpose of the research is to examine the role of farming in ensuring nutritional security and food stability based on the analysis of the Food Sustainability Index (FSI). Research methods: modeling, abstraction, analogy, analysis, synthesis, formalization, logical abstraction, theoretical cognition, systematization and classification, abstract-logical, etc. Results. Having analyzed the Food Sustainability Index for 2018, it has been established that there is a lack of a clear relationship between the pace of economic development and the level of food and nutritional sustainability. In addition, this study has identified the countries with the largest number of small farms, as well as the number of farms within the region. The correlation between the size of the farm and the area of agricultural land that it cultivates has been determined. The problems faced by small farms in the process of their activity have been analyzed. The programs implemented in the field of agro-industrial complex development by international profile institutions have been systematized. Particularly, the regional structure of agricultural development programs under the guidance of IFAD is defined, as well as the areas to which they are directed. Specific measures taken by governments to stimulate the development of small farms have been outlined. Reasonable conclusions have been formed based on the study. The direction of future research is seen in the assessment of the export potential of small farms in terms of range, volume of export deliveries and geographical direction of movement of their products.

Сучасні малі фермерські господарства є важливою ланкою в структурі світового агропромислового комплексу. Це забезпечує стабільність продовольства та харчування країни виключно на місцевому регіональному рівні. Метою дослідження є вивчення ролі сільського господарства у забезпеченні харчової безпеки та продовольчої стабільності на основі аналізу індексу харчової стійкості (FSI). Методи дослідження: моделювання, абстракція, аналогія, аналіз, синтез, формалізація, логічне абстрагування, теоретичне пізнання, систематизація та класифікація, абстрактно-логічний тощо. Результати. Проаналізувавши Індекс продовольчої стійкості за 2018 рік, було встановлено, що відсутній чіткий зв’язок між темпами економічного розвитку та рівнем продовольчої та харчової сталості. Крім того, це дослідження визначило країни з найбільшою кількістю малих фермерських господарств, а також кількість фермерських господарств у межах регіону. Визначено співвідношення між розміром господарства та площею сільськогосподарських угідь, які воно обробляє. Проаналізовано проблеми, з якими стикаються малі фермерські господарства в процесі своєї діяльності. Систематизовано програми, що реалізуються міжнародними профільними інституціями у сфері розвитку АПК. Зокрема, визначено регіональну структуру програм розвитку сільського господарства під керівництвом МФСР, а також напрямки, на які вони спрямовані. Окреслено конкретні заходи, що вживаються урядами для стимулювання розвитку малих фермерських господарств. За результатами дослідження зроблені обґрунтовані висновки. Напрям майбутніх досліджень вбачається в оцінці експортного потенціалу малих фермерських господарств за асортиментом, обсягом експортних поставок та географічним напрямком руху їх продукції.
Petrunenko I. Development of Small Farms in the Agro-Industrial Complex / I. Petrunenko, O. Pohrishchuk, M. Plotnikova, Yu. Zolotnytska, A. Dligach // International Journal of Computer Science and Network Security. - Vol.21. - No.3. - John M Jun, 2021. - P. 287-294.
Keywords: small farm; agro-industrial development programs; food and nutritional security; Food Sustainability Index; International funds; мала ферма; програми агропромислового розвитку; продовольча та харчова безпека; індекс продовольчої стійкості; міжнародні фонди; Research Subject Categories::SOCIAL SCIENCES::Business and economics::Economics